PENGARUH SKILL REPRESENTASI MENGGUNAKAN MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP LITERASI SAINS SISWA SMP - Yunanto Nur Afandi; Abdurrahman -; Agus Suyatna (Jurnal Pembelajaran Fisika, 2013)
The problem discussed in this research was influence of skill representation using contextual teaching and learning toward junior high school students’ science literacy. The purpose of this research was to determine the influence skill representation toward science literacy and increase of science literacy using contextual teaching and learning. This research was done at SMP Negeri 29 Bandarlampung using a class by the number of 38 students and using the design minimal control (One-Group Pretest-Posttest). To test the influence was done correlation and simple linear regression between the data representation and data skills posttest scientific literacy, whereas to determine the increase of science literacy was done calculation of the percentage increase in score N-gain and test of paired samples t test from data pretest and posttest of students’ science literacy. The result of this research showed that (1) there was strong and significant positive linear influence between the influence skill representation toward students’ science literacy with contribution score of 41,86% and regression equation is Y = 6,156+1,065X, and (2) there was significant increase from scientific literacy using skill representation with the increase score of 38% and the average N-gain value of 0,49 which is categorized as medium category.Kata kunci: literasi sains, pembelajaran kontekstual, skill representasi,